2020
DOI: 10.1128/aem.00464-20
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation between Broussonetia papyrifera and Its Symbiotic Fungal Community To Improve Local Adaptation of the Host

Abstract: The genetic basis of plant local adaptation has been extensively studied, yet the interplay between local adaptation, plant genetic divergence, and microbial community remains unclear. Our study used the restriction-site associated DNA sequencing (RAD-seq) approach to explore genetic divergence in Broussonetia papyrifera, and used internal transcribed spacers (ITS) to characterise fungal community. RAD-seq results show B. papyrifera individuals coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…The dominant fungal genus in fresh PM was Aureobasidium ( Figure 2B ), which has been reported to be the predominant genus on the skin of grapes ( Gao et al, 2019 ). However, inconsistent results were reported by Chen et al (2020b) , who reported that the dominant fungal genera in fresh PM were Mortierella and Hannaella . Numerous factors, such as forage types and environmental factors, result in differences in the fungal community composition ( Li et al, 2021 ).…”
Section: Resultsmentioning
confidence: 83%
“…The dominant fungal genus in fresh PM was Aureobasidium ( Figure 2B ), which has been reported to be the predominant genus on the skin of grapes ( Gao et al, 2019 ). However, inconsistent results were reported by Chen et al (2020b) , who reported that the dominant fungal genera in fresh PM were Mortierella and Hannaella . Numerous factors, such as forage types and environmental factors, result in differences in the fungal community composition ( Li et al, 2021 ).…”
Section: Resultsmentioning
confidence: 83%
“…Typically, a DM content between 25–35% and a WSC content exceeding 50 g/kg ensure an ample ensiling fermentation substrate ( Hu et al, 2009 ; Wang et al, 2018 ). JA raw material has a DM content of 35.02%, surpassing that of corn and oats, and a WSC content of 61.21 g/kg, meeting the criteria for high-quality ensiling material ( Chen et al, 2020 ; Li et al, 2022 ). The storage temperature significantly influences ensiling success ( Zhou et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Technol. 139, 125-140. doi: 10.1016/j.anifeedsci.2007 He, L., Wang, C., Xing, Y., Zhou, W., Pian, R., Chen, X., et al (2020). Ensiling characteristics, proteolysis and bacterial community of high-moisture corn stalk and stylo silage prepared with Bauhinia variegate flower.…”
Section: Data Availability Statementmentioning
confidence: 99%
“…However, the functional significance of other microbial symbioses, such as fungal endophytes, is much less understood to date [ 7 , 8 ]. Recent studies have shown that endophytic fungi play an essential role in enhancing the resistance and adaptability of host plants in grassland communities [ 9 , 10 , 11 , 12 ], but their potential impact on the host litter components and the soil environment across plant species has been largely overlooked [ 13 ].…”
Section: Introductionmentioning
confidence: 99%